Language Learning Strategies and its Implications for Second Language Teaching - Cano de Araúz, Olda (2009)
Effective language learners are aware of the strategies they use and why they use them. Likewise, skilled language learners select those strategies that work well for specific tasks. Less effective learners are also aware of their learning strategies, but employ them randomly, without a careful selection or focus of a particular strategy for an assigned task. Could less effective learners have more opportunities of becoming effective learners if they have the means of targeting their learning strategies to specific tasks? Language learning strategy instruction can help EFL students "learn better" by raising students' awareness of language learning strategies, by highlighting the relationship between strategy use and language learning tasks, and by increasing students' existing language learning strategies.